2020
DOI: 10.14233/ajchem.2020.22227
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies on Extraction of Essential Oil from Lemongrass Leaves (Cymbopogon citratus) by Steam Distillation Industrial Scale

Abstract: Study on kinetics and modeling of the essential oil steam distillation are required for the optimization of the energy requirement, parameters and the process scale-up. In this study, hydrodistillation for extraction of essential oils from lemongrass (Cymbopogon citratus) steam distillation was investigated. The recovery of essential oils was carried out on an industrial scale instrument and with with different material quantities. The experimental results are determined by the integral method of analysis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The following conditions were applied: helium as carrier gas with 36.5 cm/s of linear velocity, injector temperature of 250 °C, oven temperature program of 60-240 °C at 3 °C/min, electron energy of 70 eV, interface temperature of 250 °C. Results were compared with MS library system NIST-98 and literature data [20].…”
Section: Gc-msmentioning
confidence: 99%
See 1 more Smart Citation
“…The following conditions were applied: helium as carrier gas with 36.5 cm/s of linear velocity, injector temperature of 250 °C, oven temperature program of 60-240 °C at 3 °C/min, electron energy of 70 eV, interface temperature of 250 °C. Results were compared with MS library system NIST-98 and literature data [20].…”
Section: Gc-msmentioning
confidence: 99%
“…As a consequence, the obtained EO is negligible. As oil bath temperature increases, the effect of cavitation increases, together with the increased solubility of solutes in the solvent, leading to the rise in the amount of EO yield [20][21]. However, the excessive increase in oil bath temperature might enhance EO thermal degradation, which decreases the amount of obtained EO Besides, the short amount of extraction time can ensure the cost of the process and limit the oxidation of essential oils.…”
Section: Effect Of Oil Bath Temperaturementioning
confidence: 99%
“…It has been noted that types of extraction methods can significantly affect the number of oxidizing compounds in the essential oil [7]. Therefore, the selection of the appropriate method as well as the optimization of process parameters are also of great interest [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research objects were plants with natural flavors, such as Rutaceae plants. Some achievements have been accomplished in the extraction method and technology of plant essential oils (Dao et al., 2019; Dao, Do, et al., 2020; Dao, Ngo, et al., 2020; Dao et al., 2021). Only a few studies reported on the essential oil extraction technology and chemical substances of thuja because of the scarcity of its resources.…”
Section: Introductionmentioning
confidence: 99%